Testosterone Supplementation Induces Age-Dependent Augmentation of the Hypoxic Ventilatory Response in Male Rats With Contributions From the Carotid Bodies - Janes, Tara A.; Ambrozio-Marques, Danuzia; Fournier, Sébastien; Joseph, Vincent; Soliz, Jorge; Kinkead, Richard (Frontiers in Physiology, 2021)
Excessive carotid body responsiveness to O2 and/or CO2/H+ stimuli contributes to respiratory instability and apneas during sleep. In hypogonadal men, testosterone supplementation may increase the risk of sleep-disordered breathing; however, the site of action is unknown. The present study tested the hypothesis that testosterone supplementation potentiates carotid body responsiveness to hypoxia in adult male rats. Because testosterone levels decline with age, we also determined whether these effects were age-dependent. In situ hybridization determined that androgen receptor mRNA was present in the carotid bodies and caudal nucleus of the solitary tract of adult (69 days old) and aging (193-206 days old) male rats. In urethane-anesthetised rats injected with testosterone propionate (2 mg/kg; i.p.), peak breathing frequency measured during hypoxia (FiO2 = 0.12) was 11% greater vs. the vehicle treatment group. Interestingly, response intensity following testosterone treatment was positively correlated with animal age. Exposing ex vivo carotid body preparations from young and aging rats to testosterone (5 nM, free testosterone) 90 – 120 minutes prior to testing showed that the carotid sinus nerve firing rate during hypoxia (5% CO2 + 95% N2; 15 min) was augmented in both age groups as compared to vehicle (< 0.001% DMSO). Ventilatory measurements performed using whole body plethysmography revealed that testosterone supplementation (2 mg/kg; i.p.) 2h prior reduced apnea frequency during sleep. We conclude that in healthy rats, age-dependent potentiation of the carotid body’s response to hypoxia by acute testosterone supplementation does not favor the occurrence of apneas but rather appears to stabilize breathing during sleep.